The analysis of significant differences based on teacher demographic variables in a mandatory teacher professional development program: Implementation in a less privileged region of Indonesia - Ria Arista Asih (JEET, Journal of English Education and Technology, 2021)
This study investigated the significant differences based on teacher demographic variables in a mandatory teacher professional development (PD) program. The examined demographic variables are gender, age, academic qualification, years of teaching experience, employment status, and certification status. This information was measured through a well-developed questionnaire named the Targeted Professional Development Program. The study was conducted to 356 primary school teachers in Bima, Indonesia. Results showed that teacher perception of mandatory PD was only differed based on gender with t(354) = -1.87, p=.01. No significant differences were found pertaining teachers’ age, academic qualification, years of teaching experience, employment status, and certification status. Non-significant differences in mandatory PD perception based on teacher demography show that Indonesian mandatory PD has achieved its objectives in implementing a large-scale uniformed government PD program to support all Indonesian teachers. The only significant difference is shown through teachers’ gender, indicating that any improvement plan on future mandatory PD designs can commence by improving benefits for both male and female teachers